Rates of brain development in mammals including man. - Passingham, R (1985)
The paper considers the absolute rates at which the brain grows in different mammals and the relative rates of growth for the various subareas. It concludes that the various mammals are much more similar in the rates of growth of the brain than of the body. The rate of growth of the human brain is within the range of variation expected. Indirect evidence is presented that the different mammalian orders may differ in the relative rates of growth of the neocortex and other brain areas.